2013
DOI: 10.1093/occmed/kqt141
|View full text |Cite
|
Sign up to set email alerts
|

Associations between health and combinations of sickness presence and absence

Abstract: The results showed that combinations of frequent self-rated SP and SA are related to negative values in the four measured aspects of self-reported health 1 year later. Occupational medicine practitioners should therefore be concerned particularly with employees who report frequently occurring SP and SA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 27 publications
0
34
0
8
Order By: Relevance
“…The two papers by Lu et al, (2013 and) also used the same population; however, Lu et al, (2014) additionally included 100 Chinese respondents in the sample. One of the studies reviewed considered health outcomes in terms of sickness levels, and adopted both SP and SA as predictor variables (Gustafsson and Marklund, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two papers by Lu et al, (2013 and) also used the same population; however, Lu et al, (2014) additionally included 100 Chinese respondents in the sample. One of the studies reviewed considered health outcomes in terms of sickness levels, and adopted both SP and SA as predictor variables (Gustafsson and Marklund, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…However, while Taloyan et al, (2012) found that seven or more days of SP at baseline increased the risk of future decreased SRH; this association was attenuated to non-significance when emotional exhaustion at baseline was controlled for. When SA and SP were both adopted as predictor variables, the risks for future SRH were higher for those individuals with greater levels of sickness, regardless of their exhibited attendance behaviour (Gustafsson and Marklund, 2013).…”
Section: Self-rated Healthmentioning
confidence: 99%
“…Os resultados da pesquisa mostraram que houve uma alta prevalência de capacidade inadequada para o trabalho entre a amostra estudada (46,7%), corroborando outros estudos realizados no Brasil e no mundo com diferentes categorias profissionais 10,12,17,18,26,27 . Na presente pesquisa, apenas a variável sociodemográfica sexo apresentou associação com a capacidade inadequada para o trabalho.…”
Section: Discussionunclassified
“…Dessa forma, diferentes categorias profissionais têm sido pesquisadas quanto à sua capacidade para o trabalho no decorrer dos anos, por exemplo, trabalhadores de indústrias têxteis com diferentes turnos 11 , trabalhadores de enfermagem 10,12 , trabalhadores da área administrativa 13 , eletricitários 14 , motoristas de ônibus 15 , bombeiros 16 , professores 17 e trabalhadores em geral 18 .…”
Section: Introductionunclassified
“…Os diferenciais de maior exposição aos fatores de risco no trabalho (esforço repetitivo, equipamentos ergonomicamente pobres) e em casa (menor oportunidade de relaxar e exercitar-se fora do trabalho) podem explicar a ocorrência de absenteísmo-doença acentuado em mulheres 21 . Paradoxalmente, pesquisas apontam que as mulheres têm maiores índices de presenteísmo, definido como o ato de ir trabalhar doente, ocorrência que pode acarretar absenteísmo, sendo ambos danosos na produção do trabalho 22,23 . Mulheres são mais representadas no quantitativo de acidente de trabalho, enquanto categoria de doença profissional, do que nas de acidentes típicos ou de trajeto 24 .…”
Section: Caracterização Do Servidor Público Licenciadounclassified